ANALYSIS OF RISK FACTORS INFLUENCING THE INCIDENCE OF PNEUMONIA IN TODDLERS IN THE WORK AREA OF BATURRADEN II PUBLIC HEALTH CENTER - Shohihah, Ayidah Indana; Suratman, Suratman; Widiyanto, Agnes Fitria; Sulistyorini, Dewi (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2025)
Background: Pneumonia is the causes of death in children. Baturaden District is an area with a high incidence of pneumonia, with a prevalence rate of 4%. Pneumonia in under-five children can be caused by a variety of factors. The aim of this study was to identify factors influencing the incidence of pneumonia in under- five children in the work area of the Puskesmas Baturaden II. Methods: This study is a quantitative analysis observational study with a case- control design using a total of 108 samples consisting of 54 case samples and 54 control samples. Questionnaires, documents and stationery served as research tools. Data analysis was univariate analysis, bivariate analysis with chi-square test, and multivariate analysis with multiple logistic regression test. Results: Analysis showed that exclusive breastfeeding (p value = 0.003), the presence of smokers in the home (p value = 0.008), and the use of mosquito coils (p value = 0.045) influenced incidence pneumonia in under-five children. Nutritional status, DPT and measles vaccination status, vitamin A administration, floor type, wall type, ceiling condition, and the use of mosquito coils had no effect on the incidence of pneumonia (p value > 0.05). Conclusion: Exclusive breastfeeding is the most influential risk factor for the development of pneumonia in under-five children in the working area of Puskesmas Baturaden II. Therefore, a mother needs to increase understanding and awareness to provide exclusive breastfeeding to under-five children so that under-five children’s immunity is in good condition.